A large-scale population-based epidemiological study on the prevalence of central sensitization syndromes in Japan - Yasuo Haruyama (Nature Portfolio, 2021)
Abstract A cross-sectional study of 21,665 Japanese residents was performed to investigate the prevalence of central sensitization syndromes (CSS). CSS were assessed using the Central Sensitization Inventory (CSI-A). CSS were defined as a CSI-A score of 40 or higher. Age, sex, district, 10 CSS-related diseases (CSI-B), lifestyle, and mental factors were rated in a self-reported survey. The prevalence of CSS and its relationship with potential factors were examined by sex using descriptive and logistic regression models. The prevalence of CSS was 4.2% in all participants and was significantly higher in women (4.9%) than in men (2.7%). Adjusted odds ratios correlated with CSS for an age of 80–97 years versus 60–79 years (2.07 and 2.89), one or more CSI-B diseases (3.58 and 3.51), few sleeping hours (2.18 and 1.98), high perceived stress (5.00 and 4.91), low (2.94 and 2.71) and high (0.45 and 0.66) resilience versus moderate resilience, and exercise habits (0.68 and 0.55) in men and women (all P < 0.05). The relationship between CSS and age 20 and 59 years, ex-smokers, coffee intake, and alcohol intake differed by sex. The prevalence of CSS was estimated to be low in the healthy population. CSS correlated with CSS-related diseases and some positive and negative factors.